Answer:
I am so not good at math at all
*☆*――*☆*――*☆*――*☆*――*☆*――*☆*――*☆*――*☆**☆*――*☆*――*☆*――*☆
Answer: She messed up in Step 1
She first should of tried to factor it first. There she can see that 3 and -11 work together in order to get (x+3)(x-11)
x= -3 and x=11
Explanation:
I hope this helped!
<!> Brainliest is appreciated! <!>
- Zack Slocum
*☆*――*☆*――*☆*――*☆*――*☆*――*☆*――*☆*――*☆**☆*――*☆*――*☆*――*☆
Answer:
(3,3)
Step-by-step explanation:
x + y - 6= 0
x- y = 0
Add the two equations together
x + y - 6= 0
x- y = 0
-------------------
2x - 6 = 0
Add 6 to each side
2x-6+6 = 0
2x = 6
Divide by 2
2x/2 = 6/2
x = 3
Now find y
x-y = 0
3 - y = 0
y = 3